Gaya Komunikasi Dedy Mulyadi Ditinjau Dari Perspektif Kesantunan Berbahasa - Aulia Putri, Citra; Ramadhan, Aldi Abriansyah; Fitri Khairu, Indana Zulpa; Ade Riyanto, Andra; Asyahr, Mohammad (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This study aims to analyze the communication style of Dedy Mulyadi on his YouTube channel based on Leech’s politeness principles. The topic is significant as Dedy Mulyadi, a public figure, is known for his straightforward yet empathetic communication with the public. This research adopts a qualitative descriptive approach, using utterances from selected YouTube videos as data. The analysis applies Leech’s six maxims of politeness: tact, generosity, approbation, modesty, agreement, and sympathy. The findings reveal that Dedy Mulyadi’s communication reflects these politeness principles. He often demonstrates empathy, gives compliments, remains humble, and engages in courteous discussions. His communication not only effectively conveys messages but also fosters positive emotional connections with the community. These results indicate that politeness in language use can coexist with assertiveness in public communication. This study highlights the importance of linguistic ethics in fostering social harmony and trust, particularly in digital and public interaction spaces.